1992
DOI: 10.4141/cjps92-014
|View full text |Cite
|
Sign up to set email alerts
|

Post-flowering forage potential of spring and winter cereal mixtures

Abstract: 6,5,9,9 et7,5 et 10,9 et2O,4% inf6rieures. Bien qu'on ne connaisse pas l'ampleur de I'effet compensatoire, la meilleure qualit6 fourragbre des m6langes devrait compenser, du moins en partie, la l6gdre baisse de leur rendement de MS par rapport aux c6r6ales de printemps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 11 publications
(7 reference statements)
4
29
0
1
Order By: Relevance
“…The DM yield ha -1 for the cereal monocrops ranged from 6.3 to 7.7 t ha -1 . Bishnoi et al (1978) and Lopetinsky (1991) reported a higher yield for triticale than for other cereal crops, whereas Berkenkamp and Meeres (1987) and Baron et al (1992b) reported that oats yielded more DM ha -1 than either barley or triticale. Similar yields for triticale, barley (Spara et al 1973;Cherney and Marten 1982a;Jedel and Salmon 1994), and oats (Brown and Almodares 1976;Cherney and Marten 1982a) have also been reported.…”
Section: Yield Componentsmentioning
confidence: 99%
“…The DM yield ha -1 for the cereal monocrops ranged from 6.3 to 7.7 t ha -1 . Bishnoi et al (1978) and Lopetinsky (1991) reported a higher yield for triticale than for other cereal crops, whereas Berkenkamp and Meeres (1987) and Baron et al (1992b) reported that oats yielded more DM ha -1 than either barley or triticale. Similar yields for triticale, barley (Spara et al 1973;Cherney and Marten 1982a;Jedel and Salmon 1994), and oats (Brown and Almodares 1976;Cherney and Marten 1982a) have also been reported.…”
Section: Yield Componentsmentioning
confidence: 99%
“…However, there is limited information on nutritive value variability of swathed small grain dry matter from year to year and throughout the winter. Mixtures of small grains with other species have been used to increase nutritive value in silage and hay systems over small grains grown alone (Berkenkamp and Meeres 1987;Baron et al 1992b; Thompson et al 1992). Species that are effective for improving nutritive value in mixtures do so by adding leaf material to the small grain crop, which is usually between the heading and dough stages of development when harvested (Baron et al 1992a;Entz et al 2002).…”
mentioning
confidence: 99%
“…The presence of a non-cereal in the mixture reduced yield, but pea in the mixture with oat increased crude protein per hectare. Baron et al (1992) found that total forage yield of spring and winter cereal mixtures seeded in equal proportions was 10% lower than that of the corresponding spring cereal seeded as a monocrop when harvested at the late-milk stage. However, the spring cereal's dominance in the mixture resulted in the spring component contributing more than 50% to the dry matter yield.…”
Section: Mots Clésmentioning
confidence: 99%
“…Baron et al (1992) demonstrated that springplanted mixtures of spring and winter cereals could provide a spring silage crop, and the regrowth, primarily of the winter cereal component could provide fall pasture. However, the effect of the proportion of spring and winter cereals at seeding, and the seeding rate of the mixture has not been studied in depth.…”
Section: Mots Clésmentioning
confidence: 99%
See 1 more Smart Citation